Chemotherapy-free combination of ibrutinib and obinutuzumab for untreated advanced follicular lymphoma: results of a phase II study from the German Lymphoma Alliance - Christian Schmidt; Gabriel Scheubeck; Vindi Jurinovic; Martin Sökler; Roswitha Forstpointner; Christian Buske; Andreas Viardot; Ulrich Keller; Ullrich Graeven; Reinhard Marks; Mathias Hänel; Rüdiger Liersch; et al. (Haematologica)
Immunochemotherapy induces long-term response in patients with follicular lymphoma. However, toxicity of chemotherapy remains a relevant challenge. The Bruton’s tyrosine kinase inhibitor ibrutinib has shown significant activity in patients with indolent B-cell lymphoma. Combining ibrutinib with obinutuzumab may therefore be an attractive chemotherapy free option. We conducted a prospective, single-arm, multicenter phase 2 trial to evaluate the chemotherapy-free regimen of obinutuzumab plus ibrutinib in patients with previously untreated advanced-stage follicular lymphoma. Patients received six 21-days cycles of ibrutinib and obinutuzumab for induction and 12 additional two-month cycles for maintenance. Primary endpoint was one-year progression-free survival (PFS). The study was powered to detect an improvement of 10 percent over the one-year PFS of 85%. A total of 98 patients was enrolled in the trial. Median follow-up was 5.5 years. After induction, 5 patients (5%) had a complete response (CR) and 82 (85%) a partial response (PR). The one-year PFS was 80%, missing the prospected improvement of a one-year PFS of 85% (p=0.93). Median PFS was 4.5 years, median duration of response and overall survival were not reached. The most common adverse events of grade 3/4 were neutropenia, lung infection, hypertension, fatigue, rash and thrombocytopenia. The trial failed the primary efficacy endpoint of the chemotherapyfree regimen of obinutuzumab and ibrutinib in follicular lymphoma patients. However, the combination achieved durable and deep responses and revealed an acceptable safety profile.